Religious Disaffiliation From Orthodox Judaism: Social, Psychological, and Intellectual Factors Related to Exiting - Miles, Rona (Review of religious research, 2023)
Studies investigating disaffiliation from Orthodox Judaism typically utilize samples composed of disaffiliated individuals, without a comparison group of affiliated individuals for reference. This research investigation measured 21 social, psychological, and intellectual experiences in disaffiliated and affiliated Orthodox Jewish individuals primarily in the United States to determine which factors were predictive of disaffiliation, a type of religious change. Experiences were measured with Yes/No questions and a Likert rating scale to indicate the extent to which respondents believed each factor contributed to their disaffiliation. Participants were 730 individuals who grew up practicing Orthodox Judaism and had either stopped or continued practicing (disaffiliated N?=?387; affiliated N?=?343). Based on regression analysis, factors predictive of disaffiliation were: (1) emotional abuse, (2) feelings that Orthodoxy is restrictive, (3) diagnosis of/treatment for a psychological disorder, (4) poor secular education in school, and (5) intellectual conflicts regarding Orthodox Judaism or questioning God. When rating each factor?s contribution to their disaffiliation, exiters most frequently reported moral or social conflicts with Orthodox Judaism, intellectual conflicts regarding Orthodox Judaism or questioning God, and feelings that Orthodoxy is restrictive. These findings contribute to a more nuanced understanding of religious exiting and draw out the factors uniquely predictive of disaffiliation in this population.